Functional basis for calmodulation of the TRPV5 calcium channel. (19th January 2023) - Zuidscherwoude, Malou; van Goor, Mark K.; Roig, Sara R.; Thijssen, Niky; van Erp, Merijn; Fransen, Jack; van der Wijst, Jenny; Hoenderop, Joost G.
Abstract : Abstract: Within the transient receptor potential (TRP) superfamily of ion channels, TRPV5 is a highly Ca 2+ ‐selective channel important for active reabsorption of Ca 2+ in the kidney. Its channel activity is controlled by a negative feedback mechanism involving calmodulin (CaM) binding. Combining advanced microscopy techniques and biochemical assays, this study characterized the dynamic lobe‐specific CaM regulation. We demonstrate for the first time that functional (full‐length) TRPV5 interacts with CaM in the absence of Ca 2+, and this interaction is intensified at increasing Ca 2+ concentrations sensed by the CaM C‐lobe that achieves channel pore blocking. Channel inactivation occurs without requiring CaM N‐lobe calcification. Moreover, we show a Ca 2+ ‐dependent binding stoichiometry at the single channel level. In conclusion, our study proposes a new model for CaM‐dependent regulation – calmodulation – of this uniquely Ca 2+ ‐selective TRP channel TRPV5 that involves apoCaM interaction and lobe‐specific actions, which may be of significant physiological relevance given its role as gatekeeper of Ca 2+ transport in the kidney. Key points: The renal Ca 2+ channel TRPV5 is an important player in maintenance of the body's Ca 2+ homeostasis. Activity of TRPV5 is controlled by a negative feedback loop that involves calmodulin (CaM), a protein with two Ca 2+ ‐binding lobes. We investigated the dynamics of the interaction between TRPV5 and CaM with advanced fluorescence microscopy techniques. Our data support a new model for CaM‐dependent regulation of TRPV5 channel activity with CaM lobe‐specific actions and demonstrates Ca 2+ ‐dependent binding stoichiometries. This study improves our understanding of the mechanism underlying fast channel inactivation, which is physiologically relevant given the gatekeeper function of TRPV5 in Ca 2+ reabsorption in the kidney. Abstract : Abstract figure legend Calmodulation of the epithelial calcium channel TRPV5. The Ca 2+ concentration modulates calmodulin‐dependent inhibition of TRPV5. The three panels depict key moments in a continuum of increasing Ca 2+ concentration (gradient slider under the panels). The left panel shows a situation where Ca 2+ is virtually absent and CaM is in its apo‐CaM conformation. The interaction between TRPV5 and apo‐CaM does not rely on the presence of Ca 2+ even though CaM‐dependent inhibition of TRPV5 is compromised. The middle panel depicts a physiologically relevant Ca 2+ concentration where one or both lobes of CaM are calcified and the TRPV5‐CaM complex undergoes a conformational change that plugs the TRPV5 pore and inhibits the channel. The rightmost panel shows that increased intracellular Ca 2+ concentration stimulates the recruitment of multiple CaM molecules to active TRPV5 channels, leading to flexible binding stoichiometry. Through this mechanism CaM is able to effectively close TRPV5 channels based on the intracellular Ca 2+ concentration, preventing levels of Ca 2+ entry that could lead to cytotoxicity.